Exploring EFL Students’ Speaking Anxiety of English Teacher Education Program at One Public University in Jambi - Mukhlash Abrar; Nunung Fajaryani; Habizar Habizar; Miftahudin Miftahudin; Mercy Sokoy (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2022)
Speaking is one of the most difficult skills in language learning particularly in learning English as a foreign language. The purpose of this qualitative study was to explore the issues of speaking anxiety, the factors influencing their speaking anxiety, and the strategies they employed to alleviate the anxiety at one English teacher education program in Jambi, Indonesia. In order to collect the data, a semi-structured interview was employed and guided by an interview protocol to stimulate the participants in answering the questions during the interview. Due to the Covid-19 pandemic, we only had access to invite 12 students to participate in our study-they were nine male and three female student teachers. To select the participants, we employed purposive sampling with a convenience case strategy. Through thematic analysis (Braun and Clark, 2006), we identified three major themes of factors influencing the participants’ speaking anxiety, including 1) language barrier (Grammar, vocabulary, pronunciation, and fluency); 2) psychological issues (low motivation, and personality); and 3) learning proponents (lecturers, classmates, and unfamiliar topic). To alleviate their anxiety, the participants have undertaken strategies, such as 1) self-management (self-practice and doing positive activities) and 2) getting-help strategies (friends’ help and motivation).